Pengaruh E-service Quality terhadap Reuse Intention yang dimediasi oleh E-Satisfaction Pengguna DIGI by Bank BJB - Komalasari, Diana; Adialita, Tania (Universitas Batanghari, 2024)
Until 2022, the number of DIGI Bank BJB mobile banking users more than 849 thousand users. The frequency of DIGI transactions by Bank BJB also increased by 46 million transactions from 2021. However, research conducted by Populix in 2022 shows that DIGI by Bank BJB is not yet the main choice for customers when using mobile banking. Moreover, on PlayStore and AppStore, the DIGI by Bank bJB application only received a rating of 3.2 and 3.3 out of 5 stars respectively, and there are still complaints from users. This research aims to analyze the influence of electronic service quality on electronic satisfaction and intention to reuse the DIGI by Bank BJB application. This research uses a quantitative method obtained from survey results using a questionnaire with a Likert scale, then the statement is tested for validity and reliability and then analyzed using simple regression, multiple regression, Sobel test and T test with the help of SPSS version 25. The research sample consists of 93 respondents using the convenience sampling method and it was found that e - Satisfaction and reuse intentions can be influenced positively and significantly by the quality of e-services. In addition, e-satisfaction significantly influences reuse intention, and e-service quality influences reuse intention through e-satisfaction.